Job Hopping, Information Technology Spillovers, and Productivity Growth - Tambe, Prasanna; Hitt, Lorin M. (Management Science, 2014)
The movement of information technology (IT) workers among firms is believed to be an important mechanism by which IT-related innovations diffuse throughout the economy. We use a newly developed source of employee microdata—an online resume database—to model IT workers' mobility patterns. We find that firms derive significant productivity benefits from the IT investments of other firms from which they hire IT labor. Our estimates indicate that over the last two decades, productivity spillovers from the IT investments of other firms transmitted through this channel have contributed 20%–30% as much to productivity growth as firms' own IT investments. Moreover, we find that the productivity benefits of locating near other IT-intensive firms can primarily be explained by the mobility of technical workers within the region. Our results are unique to the flow of IT workers among firms, not other occupations, which rules out some alternative explanations related to the similarity of firms that participate in the same labor flow network. This paper was accepted by Yu (Jeffrey) Hu, guest department editor, information systems.